Lamna nasus ... - Simian, Gaëlle; Abraham, Daniel; Bailly, Nicolas; Béarez, Philippe; Urtizberea, Frank; Perrot, Axelle; Goraguer, Herle; Langlois, Robert; Daszkiewicz, Piotr; Teletchea, Fabrice; Tercerie, Sandrine; Denys, Gaël P. J. (Zenodo, 2022)
Lamna nasus (Bonnaterre, 1788) – Porbeagle – Requintaupe commun, marache or maraiche – VU ... : Published as part of Simian, Gaëlle, Abraham, Daniel, Bailly, Nicolas, Béarez, Philippe, Urtizberea, Frank, Perrot, Axelle, Goraguer, Herle, Langlois, Robert, Daszkiewicz, Piotr, Teletchea, Fabrice, Tercerie, Sandrine & Denys, Gaël P. J., 2022, Checklist of fishes from the Saint-Pierre and Miquelon archipelago, pp. 371-384 in Cybium 46 (4) on page 373, DOI: 10.26028/cybium/2022-464-005, http://zenodo.org/record/10493699 ...